2016
DOI: 10.1177/1369433216677998
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behaviour of glass fibre-reinforced polymer and ultra-high-strength fibre-reinforced concrete composite beams subjected to elevated temperature

Abstract: Composite beams consisting of pultruded glass fibre-reinforced polymer (GFRP) I-beams and ultra-high-strength fibre-reinforced concrete (UFC) slabs have been developed for use in short-span bridges. Fibre-reinforced polymer bolts (fibre-reinforced polymer threaded rods) and epoxy adhesive were used to connect the UFC slab to the GFRP I-beam. The authors conducted material tests and large-scale static bending tests at room and elevated temperatures (less than 90°C) to investigate the flexural behaviour of GFRP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Wijayawardane et al [133] also studied the pultruded GFRP I-beams flexural properties under elevated temperatures. It was reported that beams lose only 15% of their flexural strength after exposure to elevated temperatures up to 60 • C. On the other hand, they showed that both stiffness and strength deterioration increase by increasing the temperature and the failure mode was related to the wall's delamination.…”
Section: Beammentioning
confidence: 99%
“…Wijayawardane et al [133] also studied the pultruded GFRP I-beams flexural properties under elevated temperatures. It was reported that beams lose only 15% of their flexural strength after exposure to elevated temperatures up to 60 • C. On the other hand, they showed that both stiffness and strength deterioration increase by increasing the temperature and the failure mode was related to the wall's delamination.…”
Section: Beammentioning
confidence: 99%
“…Studies on concrete structures that are reinforced in the longitudinal and transversal direction using GFRP bars showed satisfactory performance in bending and shear [15][16][17][18]. Furthermore, other studies conducted experimental work on this type of reinforcement and reported the mechanical properties [19][20][21][22][23][24][25][26], physical properties [3], chemical properties [19,25,27], thermal characteristics [21,26,28], and durability properties [20,29]. These studies have been specified in CSA S807 [30], ASTM D7957 [31] material specification, and design codes to verify the quality, design, and safety of these reinforcing materials to be used as structural reinforcement.…”
Section: Structural Behavior Of Concrete Columns Reinforced With Stee...mentioning
confidence: 95%
“…Therefore, only the most remarkable works are listed here. General stress–strain analysis of the pultruded beams; 64,142,314,315,326,346,353,356363 straightening and restoration of existing beams; 246,364366 buckling instability; 247,310,342,367379 thermal loading; 380,381 and web-flange junction strength 379 are just primary examples of what composite scholars are working on in regard to the flexural behavior of full-scale pultruded structures. Other types of structural elements were also widely studied: application of composite bars and strips for reinforcement; 382389 space frame structures; 390394 hybrid beams; 79,395398 sandwich structures and bridge deck systems.…”
Section: Mechanical Properties Of Pultruded Materialsmentioning
confidence: 99%